Men who self‐harm—A scoping review of a complex phenomenon. (21st December 2021) - Tofthagen, Randi; Gabrielsson, Sebastian; Fagerström, Lisbeth; Haugerud, Lena‐Maria; Lindgren, Bitt‐Marie
Abstract: Background: To understand and care for men who self‐harm, it is important that healthcare professionals have understanding of how and why men self‐harm, men's experiences of self‐harm and what can be done to hinder or prevent self‐harm. Aims: The aim of this study was to synthesize the existing knowledge on men who self‐harm, with a special emphasis on background, self‐harming methods, experiences and reported therapeutic interventions and/or care approaches. Design: Scoping review of internationally published and grey literature, based on a methodological framework by Arksey and O'Malley. Data sources: Systematic electronic database searches were conducted in CINAHL, MEDLINE (Ovid) and PsycINFO. From a total of 684 studies found, 24 studies met the inclusion criteria: full‐text, published in English, peer‐reviewed studies and grey literature including a focus on men who self‐harm, men aged between 18 and 65 years, and published between 2010 and 2019. Results: Men's self‐harm was understood as being related to mental disorders, a means of affect regulation, a loss of self‐control, and a means of interpersonal communication. Self‐harm can be a positive or negative experience, and there is a wide variety in the methods that men use to self‐harm: sharp objects, injection, ingestion, without aids or riskful behaviour. Few studies reported on therapeutic interventions and/or care approaches for men who self‐harm. Conclusion: Men's self‐harm should be understood as a complex, socially and culturally conditioned phenomenon and studied from a multitude of perspectives. Impact: This scoping review concludes that self‐harm among men should be understood as a complex, socially and culturally conditioned phenomenon. To empower men and support their recovery from self‐harm, a person‐centred approach should be incorporated into research on the subject and practice.